Depth-of-Focus Affects 3D Perception in Stereoscopic Displays. (June 2015) - Vienne, Cyril; Blondé, Laurent; Mamassian, Pascal
Stereoscopic systems present binocular images on planar surface at a fixed distance. They induce cues to flatness, indicating that images are presented on a unique surface and specifying the relative depth of that surface. The center of interest of this study is on a second problem, arising when a 3D object distance differs from the display distance. As binocular disparity must be scaled using an estimate of viewing distance, object depth can thus be affected through disparity scaling. Two previous experiments revealed that stereoscopic displays can affect depth perception due to conflicting accommodation and vergence cues at near distances. In this study, depth perception is evaluated for farther accommodation and vergence distances using a commercially available 3D TV. In Experiment 1, we evaluated depth perception of 3D stimuli at different vergence distances for a large pool of participants. We observed a strong effect of vergence distance that was bigger for younger than for older participants, suggesting that the effect of accommodation was reduced in participants with emerging presbyopia. In Experiment 2, we extended 3D estimations by varying both the accommodation and vergence distances. We also tested the hypothesis that setting accommodation open loop by constricting pupil size could decrease the contribution of focus cues to perceived distance. We found that the depth constancy was affected by accommodation and vergence distances and that the accommodation distance effect was reduced with a larger depth-of-focus. We discuss these results with regard to the effectiveness of focus cues as a distance signal. Overall, these results highlight the importance of appropriate focus cues in stereoscopic displays at intermediate viewing distances.